Conditioned pain modulation in rodents can feature hyperalgesia or hypoalgesia depending on test stimulus intensity. Issue 4 (April 2019) - Tansley, Shannon N.; Macintyre, Leigh C.; Diamond, Laura; Sotocinal, Susana G.; George, Nicole; Meluban, Lee; Austin, Jean-Sebastien; Coderre, Terence J.; Martin, Loren J.; Mogil, Jeffrey S.
Abstract : Abstract: The counterirritation phenomenon known as conditioned pain modulation, or diffuse noxious inhibitory control in animals, is of increasing interest due to its utility in predicting chronic pain and treatment response. It features considerable interindividual variability, with large subsets of pain patients and even normal volunteers exhibiting hyperalgesia rather than hypoalgesia during or immediately after receiving a conditioning stimulus. We observed that mice undergoing tonic inflammatory pain in the abdominal cavity (the conditioning stimulus) display hyperalgesia, not hypoalgesia, to noxious thermal stimulation (the test stimulus) applied to the hindpaw. In a series of parametric studies, we show that this hyperalgesia can be reliably observed using multiple conditioning stimuli (acetic acid and orofacial formalin), test stimuli (hindpaw and forepaw-withdrawal, tail-withdrawal, hot-plate, and von Frey tests) and genotypes (CD-1, DBA/2, and C57BL/6 mice and Sprague-Dawley rats). Although the magnitude of the hyperalgesia is dependent on the intensity of the conditioning stimulus, we find that the direction of effect is dependent on the effective test stimulus intensity, with lower-intensity stimuli leading to hyperalgesia and higher-intensity stimuli leading to hypoalgesia. Abstract : Supplemental Digital Content is Available in the Text.The rodent equivalent of the phenomenon now known as conditioned pain modulation, diffuse noxious inhibitory controls, is so named because the application of pain in one part of the body produces hypoalgesia in other parts of the body. We find that using a range of stimuli hyperalgesia can be produced instead. Whether hypoalgesia or hyperalgesia is observed depends on the intensity of the test stimulus.